0278 The PESTIMAT program: development of a crop exposure matrix for pesticide exposure assessment in agriculture0278 The PESTIMAT program: development of a crop exposure matrix for pesticide exposure assessment in agriculture. (23rd June 2014) - Baldi, Isabelle; Carles, Camille; Cantagrel, Anne; Lecluse, Yannick; Niez, Elodie; Fabbro-Peray, Pascale; Lebailly, Pierre
Abstract : Objectives: Pesticides include ˜1000 chemicals with various toxicological properties. Pesticide exposure assessment represents a crucial methodological issue for epidemiological studies. A reconstitution of pesticides used in entire professional careers based only on the memory is questionable. PESTIMAT is a crop exposure matrix, which intends to reconstitute parameters of pesticide exposure in France. Method: PESTIMAT is made of tables crossing crops and active ingredients (a.i.) by year from 1950 to 2010 and providing the following exposure parameters: 1) probability corresponding to the proportion of farmers having used the a.i. (in%), 2) frequency expressed as the number of treatment days, 3) intensity documented by the application rate of the a.i. (in kg/ha). Parameters were obtained by the combination of six complementary sources: i) registrations and withdrawals from the Agriculture Ministry, ii) information from ACTA* on products marketed iii) agricultural recommendations by the Plant Health Protection body, iv) treatment calendars provided by farmers, v) information from professionnal associations of farmers, vi) data from the industry Results: To date, 529 a.i. usable between 1950 and 2010 on 4 crops are included in PESTIMAT, corresponding to 160 fungicides (30%), 160 herbicides (30%) and 209 insecticides (40%). The total numbers were comparable on wheat/barley (N = 293), vineyards (N = 280), and apple-growing (N = 267) but lower on corn (N = 196). We will present an illustration with data obtained for dithiocarbamates fungicides, and examples of use in epidemiological studies, e.g. PHYTONER and AGRICAN cohorts. Conclusions: The multisource information available in the PESTIMAT matrix should enable to assess associations between pesticides and health at the a.i. level.